Transformation of Ulva mutabilis (Chlorophyta) by vector plasmids integrating into the genome. Issue 5 (18th September 2015) - Oertel, Wolfgang; Wichard, Thomas; Weissgerber, Adelheid
Abstract : A method for the stable transformation of the green marine macroalga Ulva mutabilis was developed based on vector plasmids integrating into the genome. By combination of the expression signals (promoter, enhancer, and transcriptional termination sequences) of a chromosomal rbcS gene from U. mutabilis with the bleomycin resistance gene ( ble ) from Streptoalloteichus hindustanus, a dominant selectable marker gene was constructed for the preparation of a series of E. coli — U. mutabilis shuttle vector plasmids. Special vectors were prepared for the introduction and expression of foreign genes in Ulva, for insertional mutagenesis and gene tagging by plasmid integration into the genome, and for protein tagging by the green fluorescent protein, as well as tools for posttranscriptional gene silencing and cosmid cloning to prepare genomic gene libraries for mutant gene complementation. The vectors were successfully tested in pilot experiments, where they were efficiently introduced into Ulva gametes, zoospores or protoplasts of somatic blade cells by treatment with Ca 2+ ‐ions and polyethylene glycol under isotonic conditions at low ionic strength. The parthenogenetically propagated phleomycin‐resistant transformants of the mutant slender (sl) and the wildtype (wt) were demonstrated to be carrying the plasmids randomly integrated into the chromosomes often as tandem repeat clusters.